A scoping review of arts in mental health policy in the United States - Alexandra K. Rodriguez; Alexandra K. Rodriguez; Jennifer L. Kuo; Cris Sanhueza; Gray Davidson Carroll; Courtney Pyche; Jane Morgan-Daniel; George Hack; Jill Sonke (Frontiers in Public Health)
The mental health crisis in the United States has been exacerbated with the emergence of the loneliness epidemic and resurgence of mental health inequities. To address the scope of this crisis comprehensively and equitably, a socioecological, cross-sectoral approach is necessary. While arts in mental health strategies have been employed internationally and nationally for preventative and rehabilitative mental health support, there remains limited knowledge of policy in the US to sustain and expand arts in mental health practices. Subsequently, this review sought to understand what priorities and strategies are employed in public health policies that seek to engage the arts to address mental health in the United States. Fourteen databases — inclusive of Embase, PsycINFO, PubMed, Scopus, and PolicyFile — were searched alongside a comprehensive grey literature search. Included documents were originated by a US organization or agency, included a mode and form of arts participation, had a focus on mental health, maintained a public health purview, pertain to the United States, and can be considered a policy document. Of 4,958 identified documents, 29 met inclusion criteria and were included. Following extraction, the evidence revealed several salient results: (a) the relative nascency of arts in mental health policy documents in the United States; (b) that policy recommendations primarily center on creating sustained, collective action and leveraging funding; and (c) that the arts sector alongside the arts and health sector are primarily leading policy work. Current momentum in the United States offers a “policy window” as there is alignment, as evidenced in this review, amongst national policy makers, the prevailing mental health crisis, and opportunities for arts in mental health policies as a viable solution. As such, this work can be mobilized to strategize how to best engage or promote the engagement of local artists, mental health practitioners, arts in mental health researchers, and policy makers in the development of arts in mental health policies moving forward. Future work should seek to intentionally build on areas of sustained effort to effectively catalyze future work towards developing legislative, regulative, or even litigative cross-sectoral, arts in mental health policies.